Dispersion agent for new energy and preparation method thereof

By combining biomass composites, polyacrylic acid, cellulose mixture, surfactant and antioxidant in the decoupling agent for new energy batteries, the problems of slow decoupling rate and insufficient safety of existing decoupling agents are solved. , achieving faster degluing rate, better antioxidant capacity and higher safety.

CN119490894AActive Publication Date: 2025-02-21中山市卡施力顿建材有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411424694.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-21
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The degluing rate of existing new energy batteries is slow, and the organic solvents are highly volatile, flammable and explosive, and corrosive to equipment, affecting the environment and safety.

Method used

A new energy decoction agent was prepared by combining biomass composites, polyacrylic acid, cellulose mixture, surfactant and antioxidant. Biomatrix composites contain active groups, which can destroy the chemical bonds of the adhesive and improve the degluing rate; polyacrylic acid reduces the adhesiveness of the adhesive and promotes the uniformity of the antioxidant; surfactants improve wetting ability and permeability.

Benefits of technology

Significantly improve the glue understanding rate, enhance the antioxidant ability, improve the stability and compatibility of glue understanding agents, reduce the harm to the environment and equipment, and improve the performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081824840000141
    Figure BDA0005081824840000141
Patent Text Reader

Abstract

The invention relates to the technical field of battery dispergators, in particular to a dispergator for new energy and a preparation method thereof.According to the dispergator for the new energy, which is relatively high in dispergation rate, is prepared by compounding a bio-based compound, polyacrylic acid, a cellulose mixture, a surfactant, a solvent and an antioxidant. Wherein carboxyl groups in polyacrylic acid molecules interact with charges on the surfaces of colloidal particles, so that interaction force among the colloidal particles can be weakened, and aggregation of the colloidal particles is promoted; molecules of the bio-based compound and cellulose mixture contain active groups such as carboxyl, hydroxyl and the like, chemical bonds in the adhesive can be broken, the cohesiveness of the adhesive can be reduced, intermolecular hydrogen bonds and Van der Waals force can be formed, the interaction force can be enhanced, and the structural stability of the dispergator can be improved; the raw materials are easy to obtain, good compatibility and biodegradability are achieved, environmental protection benefits are achieved, and compared with the prior art, wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery disintegrators, and in particular to a disintegrator for new energy and a preparation method thereof. Background Art

[0002] New energy generally refers to renewable energy developed and utilized on the basis of new technologies, including solar energy, biomass energy, wind energy, geothermal energy, wave energy, ocean current energy and tidal energy, as well as thermal cycles between the ocean surface and deep layers; in addition, there are hydrogen energy, biogas, alcohol, methanol and other new energy sources that refer to energy forms that can replace traditional energy, such as solar energy, wind energy, hydropower, geothermal energy, etc. In the field of new energy materials, especially in the manufacturing process of photovoltaics, batteries and advanced composite materials, disintegrators, as key auxiliary materials, play an indispensable role.

[0003] During the battery manufacturing process, the electrode sheet will be coated with a layer of colloid to adhere to the active material, electrode material, current collector and other battery components. For example, polyvinylidene fluoride (PVDF) is the most commonly used oily binder in lithium-ion batteries, with good anti-oxidation and reduction ability and thermal stability; silicone rubber adhesive is used in the bonding of cover sheets and battery sheets on spacecraft solar cells; perfluoro copolymer (FEP), polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE) adhesives are often used in the negative electrode molding process of nickel-hydrogen batteries. The choice of adhesive has a direct impact on the performance, safety and durability of the battery. However, in the subsequent assembly process, this layer of colloid needs to be removed to facilitate the assembly of the electrode sheet and the contact of the active material. This requires the use of a debonding agent.

[0004] Traditional debonding agents are mainly composed of organic solvents, such as alcohols, ketones, ethers, etc. However, existing debonding agents for new energy batteries have some shortcomings. First, these organic solvents are highly volatile and may cause harm to the environment and operators during use. Secondly, these organic solvents have low flash points and are flammable and explosive, which increases the safety risks in the production process. Thirdly, some organic solvents are highly corrosive to equipment and may cause damage to production equipment. Finally, the debonding effect of these organic solvents is not ideal and may affect the performance of the battery.

[0005] In the prior art, some existing new energy disintegrators, such as patent technology document CN118562566A, disclose a disintegrator for new energy batteries, which includes the following raw materials by weight: esterified polyvinyl alcohol, 5-10 parts; hydroxyethyl methylcellulose, 3-7 parts; plant modifier, 5-10 parts; propylene glycol, 8-12 parts; xylene, the balance, the plant modifier includes esterified cellulose, esterified lignin, esterified vegetable oil and esterified vegetable wax. This invention reduces the production cost by adding plant modifiers, and also has certain environmental benefits, but the disintegration rate of the disintegrator in this invention needs to be improved.

[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop a new energy disintegrator with a faster disintegration rate and a preparation method thereof. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a new energy disintegrator and a preparation method thereof, so as to solve the problem of slow disintegration rate of new energy disintegrator in the prior art.

[0008] Based on the above purpose, the present invention provides a new energy disintegrator and a preparation method thereof. The new energy disintegrator is prepared from the following raw materials in parts by weight:

[0009] 1-3 parts of bio-based composite, 0.5-2 parts of cellulose mixture, 0.3-1.0 parts of polyacrylic acid, 5-8 parts of surfactant A, 7-12 parts of surfactant B, 1-2 parts of antioxidant, 78-86 parts of solvent;

[0010] The bio-based composite is obtained by mixing polylactic acid, starch, lignin, modified chitin and deionized water in a mass ratio of 2-3:3-6:2-3:5-8:2-5. The bio-based composite contains active groups that can destroy the chemical bonds between adhesive molecules and increase the debonding rate of the debonding agent.

[0011] The cellulose polymer is obtained by mixing ethyl cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 4-8:2-6:2-6;

[0012] The surfactant A is any one of N-octyl pyrrolidone, diester phosphate, and lauryl ether phosphate;

[0013] The surfactant B is any one of nonionic alcohol ethoxylate, polyethyleneimine alkoxy compound and sodium perfluorononenyloxybenzenesulfonate.

[0014] Preferably, the method for preparing the modified chitin comprises the following steps:

[0015] Step A1. Add hydrochloric acid to N,N-dimethylformamide, add chitin to a flask containing N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add phthalic anhydride, heat and stir to obtain a mixture A;

[0016] Step A2. Add sodium hydroxide to mixture A to neutralize excess hydrochloric acid in mixture A, stir evenly, then add phenol anhydride, heat and stir to obtain mixture B;

[0017] Step A3. Sodium bicarbonate was added to the mixture B, and the gel was filtered to obtain a gel, which was washed twice with deionized water, ground and freeze-dried at -10°C for 4-4.5 hours to obtain modified chitin.

[0018] Preferably, the mass ratio of N,N-dimethylformamide, hydrochloric acid, chitin and phthalic anhydride in step A1 is 5-7:5-7:4-8:12-15;

[0019] The temperature during the heating and stirring is 55-60° C., and the stirring time is 2-2.5 hours.

[0020] Preferably, in step A2, the mass ratio of the mixture A, sodium hydroxide and phenolic anhydride is 4-7:2-3:16-20;

[0021] The temperature during heating and stirring is 55-60°C, and the stirring time is 2.5-3h;

[0022] The mass ratio of the mixture B to sodium bicarbonate in step A3 is 5-8:7-10.

[0023] Preferably, the method for preparing the bio-based composite comprises the following steps:

[0024] Polylactic acid, starch, lignin, modified chitin and deionized water are ultrasonically treated for 10-15 minutes and mixed evenly to obtain a bio-based composite.

[0025] Preferably, the molecular weight of the polyacrylic acid is 30,000-50,000 g / mol. The carboxyl groups in the polyacrylic acid molecules interact with the charges on the surface of the colloid particles, which can weaken the interaction force between the colloid particles, promote the aggregation of the colloid particles, and reduce the adhesion of the adhesive.

[0026] Preferably, the solvent is obtained by mixing N,N-dimethylformamide, dimethyl sulfoxide, xylene and ethanol in a mass ratio of 5-8:5-8:20-30:10-12.

[0027] Preferably, the antioxidant is obtained by mixing butylated hydroxytoluene and propyl gallate in a mass ratio of 3-7:10-15.

[0028] Preferably, the method for preparing the cellulose mixture comprises the following steps:

[0029] Ethyl cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose are uniformly mixed to obtain a cellulose mixture.

[0030] A method for preparing a new energy dissolving agent comprises the following steps:

[0031] Step S1. Add the bio-based composite to a reaction kettle containing a solvent, heat to 50-60° C., stir for 40-60 min at a stirring rate of 30-60 r / min, mix evenly, then add the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0032] Step S2. Add polyacrylic acid to the mixture C, continue stirring for 20-40 minutes, then add surfactant A, surfactant B and antioxidant, stir for 55-75 minutes, and cool to room temperature to obtain a new energy disintegrator.

[0033] Beneficial effects of the present invention:

[0034] The present invention provides a new energy disintegrator and a preparation method thereof. The present invention prepares a new energy disintegrator with a fast disintegration rate by compounding a bio-based composite, polyacrylic acid, a cellulose mixture, a surfactant and an antioxidant.

[0035] Among them, the carboxyl groups in the polyacrylic acid molecules interact with the charges on the surface of the colloidal particles, which can weaken the interaction force between the colloidal particles, promote the aggregation of the colloidal particles, and reduce the viscosity of the adhesive. In addition, polyacrylic acid can be used as a dispersant to promote the uniformity of the antioxidant in the degumming agent, increase the contact rate between the antioxidant and the free radicals, and thus effectively enhance the overall antioxidant capacity of the degumming agent. The degumming agent has good stability between molecules and can better play a degumming role.

[0036] Surfactant A and surfactant B can both reduce the surface tension of the disintegrator, so that the disintegrator has good wetting ability and permeability, and the interaction force between the disintegrator and the adhesive molecules is also enhanced, and the disintegration rate is improved; xylene and ethanol in the solvent are volatile and well-soluble organic solvents. The principle of like dissolves like is used in the disintegrator to improve the solubility of materials such as polyacrylic acid, and it also has good compatibility with them and is easy to remove.

[0037] The molecules of the bio-based composite and cellulose mixture contain active groups such as carboxyl and hydroxyl groups, which may react chemically with the adhesive molecules to break the chemical bonds in the adhesive, and may form intermolecular hydrogen bonds and van der Waals forces, thereby enhancing the interaction force and improving the structural stability of the disintegrator. On the other hand, the bio-based composite and cellulose mixture have good biodegradability while having cheap raw materials and good compatibility, and also have a significant effect on environmental protection. Therefore, the new energy disintegrator prepared in the present invention has good overall compatibility, good stability, and a faster disintegration rate. Compared with the prior art, it has broad application prospects. DETAILED DESCRIPTION

[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0039] The sources and properties of some of the raw materials used in the present invention are as follows:

[0040] Chitin was purchased from Jiangsu Bernas New Materials Co., Ltd.; hydrochloric acid was purchased from Xilong Science Co., Ltd.; N,N-dimethylformamide was purchased from Wuhan Kemik Biomedical Technology Co., Ltd.; phthalic anhydride was purchased from Shijiazhuang Bailong Chemical Co., Ltd.; sodium hydroxide was purchased from Dunhuang Mingduo Chemical Co., Ltd.; phenol anhydride was purchased from Panjin Qilu Chemical Co., Ltd.; sodium bicarbonate was purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd.; polyacrylic acid was purchased from Shanghai Yiji Biological Reagent Co., Ltd.; corn starch was purchased from China Starch Holdings Co., Ltd.; lignin was purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.; carboxymethyl cellulose was purchased from Nantong Runfeng Petrochemical Co., Ltd.; dimethyl sulfoxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; sodium dodecylbenzenesulfonate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; dibutylhydroxytoluene was purchased from Yuanzheng Bioengineering Co., Ltd.; propyl gallate was purchased from Hebei Kelongduo Biotechnology Co., Ltd.; N-octyl pyrrolidone was purchased from Hubei Mackays Fine Chemical Technology Co., Ltd.

[0041] Embodiment 1: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0042] S1. Add 5 g of hydrochloric acid to 5 g of N,N-dimethylformamide, add 4 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 12 g of phthalic anhydride, heat and stir at 55°C for 2.5 h to obtain a mixture A;

[0043] S2. Add 2 g of sodium hydroxide to 4 g of mixture A, stir evenly, then add 16 g of phenol anhydride, heat and stir at 55 ° C for 3 h to obtain a mixture B;

[0044] S3. 7 g of sodium bicarbonate was added to 5 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4 h to obtain modified chitin;

[0045] S4. 2 g of polylactic acid, 3 g of starch, 2 g of lignin, 5 g of modified chitin and 2 g of deionized water were ultrasonically treated for 10 min and mixed to obtain a bio-based composite;

[0046] S5. 4 g of ethyl cellulose, 2 g of hydroxymethyl cellulose and 2 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0047] S6. Add 1 g of the bio-based composite to a reactor containing 78 g of solvent, heat to 50° C., stir for 60 min at a stirring rate of 60 r / min, mix well, add 0.5 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0048] S7. Add 0.3 g of polyacrylic acid to mixture C, continue stirring for 20 min, then add 5 g of N-octyl pyrrolidone, 7 g of fatty alcohol polyoxyethylene ether-9 and 1 g of antioxidant, stir for 55 min, and cool to room temperature to obtain a new energy disintegrator.

[0049] Embodiment 2: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0050] S1. Add 6 g of hydrochloric acid to 5 g of N,N-dimethylformamide, add 5 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 12 g of phthalic anhydride, heat and stir at 57°C for 2.5 h to obtain a mixture A;

[0051] S2. Add 2 g of sodium hydroxide to 5 g of mixture A, stir evenly, then add 18 g of phenol anhydride, heat and stir at 56 ° C for 3 h to obtain a mixture B;

[0052] S3. 8 g of sodium bicarbonate was added to 5 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4 h to obtain modified chitin;

[0053] S4. 3 g of polylactic acid, 3 g of starch, 3 g of lignin, 8 g of modified chitin and 5 g of deionized water were ultrasonically treated for 10 min and mixed to obtain a bio-based composite;

[0054] S5. 4 g of ethyl cellulose, 6 g of hydroxymethyl cellulose and 6 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0055] S6. Add 1 g of the bio-based composite to a reactor containing 80 g of solvent, heat to 50° C., stir for 45 min at a stirring rate of 35 r / min, mix well, then add 2 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0056] S7. Add 1.0 g of polyacrylic acid to mixture C, continue stirring for 25 min, then add 8 g of N-octyl pyrrolidone, 12 g of fatty alcohol polyoxyethylene ether-9 and 2 g of antioxidant, stir for 60 min, and cool to room temperature to obtain a new energy disintegrator.

[0057] Embodiment 3: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0058] S1. Add 7 g of hydrochloric acid to 5 g of N,N-dimethylformamide, add 6 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 13 g of phthalic anhydride, heat and stir at 58°C for 2.5 h to obtain a mixture A;

[0059] S2. Add 2 g of sodium hydroxide to 6 g of mixture A, stir evenly, then add 18 g of phenol anhydride, heat and stir at 57 ° C for 3 h to obtain a mixture B;

[0060] S3. Add 10 g of sodium bicarbonate to 5 g of mixture B, filter to obtain a gel, wash twice with deionized water, grind and freeze-dry at -10 ° C for 4 h to obtain modified chitin;

[0061] S4. 2 g of polylactic acid, 6 g of starch, 2 g of lignin, 7 g of modified chitin and 4 g of deionized water were ultrasonically treated for 10-15 min and mixed to obtain a bio-based composite;

[0062] S5. 8 g of ethyl cellulose, 2 g of hydroxymethyl cellulose and 6 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0063] S6. Add 3 g of the bio-based composite to a reactor containing 82 g of solvent, heat to 55° C., stir for 50 min at a stirring rate of 40 r / min, mix well, add 0.5 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0064] S7. Add 0.3 g of polyacrylic acid to mixture C, continue stirring for 30 min, then add 5 g of N-octyl pyrrolidone, 7 g of fatty alcohol polyoxyethylene ether-9 and 1 g of antioxidant, stir for 60 min, and cool to room temperature to obtain a new energy disintegrator.

[0065] Embodiment 4: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0066] S1. Add 5 g of hydrochloric acid to 6 g of N,N-dimethylformamide, add 6 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 14 g of phthalic anhydride, heat and stir at 58°C for 2.5 h to obtain a mixture A;

[0067] S2. Add 2.5 g of sodium hydroxide to 4 g of mixture A, stir evenly, then add 18 g of phenol anhydride, heat and stir at 58 ° C for 3 h to obtain a mixture B;

[0068] S3. 7 g of sodium bicarbonate was added to 7 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4.5 h to obtain modified chitin;

[0069] S4. 3 g of polylactic acid, 5 g of starch, 2.5 g of lignin, 5 g of modified chitin and 3 g of deionized water were ultrasonically treated for 12 min and mixed to obtain a bio-based composite;

[0070] S5. 8 g of ethyl cellulose, 6 g of hydroxymethyl cellulose and 2 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0071] S6. Add 2 g of the bio-based composite to a reactor containing 84 g of solvent, heat to 60° C., stir for 50 min at a stirring rate of 45 r / min, mix well, then add 1 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0072] S7. Add 0.8 g of polyacrylic acid to mixture C, continue stirring for 35 min, then add 6 g of N-octyl pyrrolidone, 9 g of fatty alcohol polyoxyethylene ether-9 and 1.5 g of antioxidant, stir for 65 min, and cool to room temperature to obtain a new energy disintegrator.

[0073] Embodiment 5: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0074] S1. Add 6 g of hydrochloric acid to 6 g of N,N-dimethylformamide, add 7 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 15 g of phthalic anhydride, heat and stir at 60°C for 2 h to obtain a mixture A;

[0075] S2. Add 2.5 g of sodium hydroxide to 7 g of mixture A, stir evenly, then add 20 g of phenol anhydride, heat and stir at 59 ° C for 2.5 h to obtain a mixture B;

[0076] S3. 10 g of sodium bicarbonate was added to 7 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4.5 h to obtain modified chitin;

[0077] S4. 2.5 g of polylactic acid, 5 g of starch, 2.5 g of lignin, 7 g of modified chitin and 3 g of deionized water were ultrasonically treated for 15 min and mixed to obtain a bio-based composite;

[0078] S5. 6 g of ethyl cellulose, 4 g of hydroxymethyl cellulose and 4 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0079] S6. Add 2 g of the bio-based composite to a reactor containing 84 g of solvent, heat to 60° C., stir for 40 min at a stirring rate of 60 r / min, mix well, then add 2 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0080] S7. Add 0.5 g of polyacrylic acid to mixture C, continue stirring for 40 min, then add 7 g of N-octyl pyrrolidone, 10 g of fatty alcohol polyoxyethylene ether-9 and 2 g of antioxidant, stir for 75 min, and cool to room temperature to obtain a new energy disintegrator.

[0081] Embodiment 6: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0082] S1. Add 7 g of hydrochloric acid to 7 g of N,N-dimethylformamide, add 8 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 15 g of phthalic anhydride, heat and stir at 60 ° C for 2 h to obtain a mixture A;

[0083] S2. Add 3 g of sodium hydroxide to 4 g of mixture A, stir evenly, then add 16 g of phenol anhydride, heat and stir at 60 ° C for 2.5 h to obtain a mixture B;

[0084] S3. 7 g of sodium bicarbonate was added to 8 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4.5 h to obtain modified chitin;

[0085] S4. 3 g of polylactic acid, 6 g of starch, 2 g of lignin, 8 g of modified chitin and 3 g of deionized water were ultrasonically treated for 15 min and mixed to obtain a bio-based composite;

[0086] S5. 6 g of ethyl cellulose, 4 g of hydroxymethyl cellulose and 4 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0087] S6. Add 3 g of the bio-based composite to a reactor containing 86 g of solvent, heat to 60° C., stir for 40 min at a stirring rate of 60 r / min, mix well, then add 2 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0088] S7. Add 0.3 g of polyacrylic acid to mixture C, continue stirring for 40 min, then add 8 g of N-octyl pyrrolidone, 7 g of fatty alcohol polyoxyethylene ether-9 and 1 g of antioxidant, stir for 70 min, and cool to room temperature to obtain a new energy disintegrator.

[0089] Embodiment 7: A method for preparing a dissolving agent for new energy, comprising the following steps:

[0090] S1. Add 5 g of hydrochloric acid to 7 g of N,N-dimethylformamide, add 8 g of chitin to a flask containing the N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add 12 g of phthalic anhydride, heat and stir at 60°C for 2.5 h to obtain a mixture A;

[0091] S2. Add 3 g of sodium hydroxide to 7 g of mixture A, stir evenly, then add 20 g of phenol anhydride, heat and stir at 60 ° C for 2.5 h to obtain a mixture B;

[0092] S3. 10 g of sodium bicarbonate was added to 8 g of mixture B, the gel was filtered, washed twice with deionized water, ground and freeze-dried at -10 ° C for 4.5 h to obtain modified chitin;

[0093] S4. 3 g of polylactic acid, 5 g of starch, 3 g of lignin, 6 g of modified chitin and 5 g of deionized water were ultrasonically treated for 15 min and mixed to obtain a bio-based composite;

[0094] S5. 4 g of ethyl cellulose, 4 g of hydroxymethyl cellulose and 4 g of hydroxyethyl cellulose were mixed to obtain a cellulose mixture;

[0095] S6. Add 2.5 g of the bio-based composite to a reactor containing 86 g of solvent, heat to 60° C., stir at a stirring rate of 55 r / min for 45 min, mix well, then add 1 g of the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C;

[0096] S7. Add 0.7 g of polyacrylic acid to mixture C, continue stirring for 40 min, then add 8 g of N-octyl pyrrolidone, 9 g of fatty alcohol polyoxyethylene ether-9 and 2 g of antioxidant, stir for 75 min, and cool to room temperature to obtain a new energy disintegrator.

[0097] Comparative Example 1:

[0098] Compared with Example 1, in this comparative example, polyacrylic acid is not added during the preparation of the new energy dissolving agent, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the new energy dissolving agent is obtained.

[0099] Comparative Example 2:

[0100] Compared with Example 1, the present comparative example does not add the bio-based composite material during the preparation process of the new energy dissolving agent, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the new energy dissolving agent is obtained.

[0101] Comparative Example 3:

[0102] Compared with Example 1, the cellulose mixture was not added in the preparation process of the new energy dissolving agent in this comparative example, and the remaining steps and parameters were the same, which will not be repeated in this comparative example, and finally the new energy dissolving agent was obtained.

[0103] Comparative Example 4:

[0104] Compared with Example 1, this comparative example only replaces "N-octyl pyrrolidone" with "an equal amount of fatty alcohol polyoxyethylene ether-9", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a disintegrator for new energy is obtained.

[0105] Comparative Example 5:

[0106] Compared with Example 1, this comparative example only replaces "fatty alcohol polyoxyethylene ether-9" with "an equal amount of N-octyl pyrrolidone", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a disintegrator for new energy is obtained.

[0107] Performance Test:

[0108] Environmental performance test:

[0109] Take 100g of the new energy dispersants prepared in Examples 1 to 7 and Comparative Examples 1 to 5, respectively, and test the organic matter content. According to the test results, calculate the organic matter emission of each dispersant;

[0110] Conductive test: Take 100g of the new energy dispersant prepared in Examples 1 to 7 and Comparative Examples 1 to 5 respectively, and test it using a DC resistance tester;

[0111] Non-flammability test:

[0112] Take 100g of the new energy dispersants prepared in Examples 1 to 7 and Comparative Examples 1 to 5 respectively, and conduct a combustion test to observe whether each dispersant burns;

[0113] Debonding speed test: 100 g of the new energy debonding agent prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were respectively taken and applied on the standard adhesive, and then the debonding speed test was performed under a constant temperature and humidity environment, and the debonding conditions of the debonding agent were recorded respectively;

[0114] Table 1 Summary of experimental data in Example 1 to Example 7 and Comparative Examples 1 to Comparative Examples 5

[0115]

[0116] Data Analysis:

[0117] As can be seen from Table 1, the new energy disintegrator prepared by the present invention has a faster disintegration rate. This may be due to the interaction between the carboxyl groups in the polyacrylic acid molecules and the charges on the surface of the colloid particles, which can weaken the interaction between the colloid particles and promote the aggregation of the colloid particles, thereby reducing the viscosity of the adhesive. The bio-based composite and cellulose mixture molecules contain active groups such as carboxyl groups and hydroxyl groups, which may react chemically with the adhesive molecules to break the chemical bonds in the adhesive, and may form intermolecular hydrogen bonds and van der Waals forces, thereby enhancing the interaction and improving the structural stability of the disintegrator. On the other hand, they may also react with the electric charge to form a bond. Chemical bonds are formed in the battery material to improve the discharge performance of the battery. At the same time, the bio-based composite and cellulose mixture will also improve the flame retardancy of the disintegrator; fatty alcohol polyoxyethylene ether-9 and N-octyl pyrrolidone are two surfactants that can reduce the surface tension of the disintegrator, so that the disintegrator has good wetting ability and permeability, and the interaction force between the disintegrator and the adhesive molecules is also enhanced, and the disintegration rate is improved; xylene and ethanol in the solvent are volatile and well-soluble organic solvents. The principle of like dissolves in like is used in the disintegrator to improve the solubility of materials such as polyacrylic acid, and it also has good compatibility with it and is easy to remove;

[0118] In Comparative Example 1, since no polyacrylic acid was added during the preparation of the new energy dissolving agent, it can be seen from Table 1 that its dissolving rate is relatively slow. This may be due to the interaction between the carboxyl groups in the polyacrylic acid molecules and the charges on the surface of the colloid particles, which can weaken the interaction between the colloid particles. At the same time, the spatial structure of the polyacrylic acid molecular chain enables it to form a network structure between the colloid particles, promoting the aggregation of the colloid particles, thereby reducing the viscosity of the adhesive; and polyacrylic acid can be used as a dispersant to promote the uniformity of the antioxidant in the dissolving agent, increase the contact rate between the antioxidant and the free radicals, and thus effectively improve the overall antioxidant capacity of the dissolving agent, and the molecular structure of the dissolving agent is improved. The stability is good and the disintegration effect can be better exerted. Therefore, the disintegration rate of comparative example 1 is slower than that of embodiment 1. Since no bio-based composite material is added in the preparation process of the disintegrator for new energy in comparative example 2, it can be seen from Table 1 that its disintegration rate is slower. This may be because the modified chitin has undergone two acetylation reactions and has amphiphilicity, which makes the bio-based composite material molecules have good compatibility. In addition, starch, lignin and polylactic acid are biomacromolecules and contain more active groups, which can break the chemical bonds in the adhesive molecules and reduce the bonding performance. Moreover, these active groups can form hydrogen bonds and van der Waals forces with the cellulose mixture and polyacrylic acid to enhance the compatibility of each material. The interaction force between the substances improves the structural stability of the disintegrator and prevents rupture or leakage during the disintegration process; these active groups may also form chemical bonds with the battery materials to enhance the discharge performance of the battery, so the disintegration rate of Comparative Example 2 is slower than that of Example 1; Comparative Example 3 does not add the cellulose mixture during the preparation of the new energy disintegrator, and it can be seen from Table 1 that its disintegration rate is slower. This may be because the cellulose mixture contains ethyl cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose, and the groups contained therein can also react chemically with the adhesive molecules, which can break the chemical bonds in the adhesive molecules, reduce the bonding performance, and react with the bio-based composite. Hydrogen bonds and van der Waals forces are formed between substances, the interaction forces between substances are enhanced, and the structural stability of the disintegrator is improved. Therefore, the disintegration rate shown in Comparative Example 3 is slower than that in Example 1. Since "N-octyl pyrrolidone" is replaced by "an equal amount of fatty alcohol polyoxyethylene ether-9" in Comparative Example 4, it can be seen from Table 1 that its disintegration rate is slower. This may be because the surfactant AN-octyl pyrrolidone is a solvent-based surfactant, which has the ability to swell the disintegrator and the ability of rapid wetting of the surfactant, so that the adhesive is accelerated to swell and the disintegration rate of the disintegrator is accelerated. Therefore, the disintegration rate shown in Comparative Example 4 is slower than that in Example 1.In Comparative Example 5, since "fatty alcohol polyoxyethylene ether-9" is replaced by "equal amount of N-octyl pyrrolidone", it can be seen from Table 1 that its degumming rate is slower. This may be because the surfactant B, fatty alcohol polyoxyethylene ether-9, has a certain cleaning effect and excellent wetting speed. While improving the solution wetting speed and degumming rate, it can also peel and suspend the silicon powder on the surface of the silicon wafer to a certain extent during degumming. Therefore, the degumming rate shown in Comparative Example 5 is slower than that in Example 1. ;

[0119] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0120] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A new energy dissolving agent, characterized in that: It is composed of the following raw materials in parts by weight: 1-3 parts of bio-based composite, 0.5-2 parts of cellulose mixture, 0.3-1.0 parts of polyacrylic acid, 5-8 parts of surfactant A, 7-12 parts of surfactant B, 1-2 parts of antioxidant, 78-86 parts of solvent; The bio-based composite is obtained by mixing polylactic acid, starch, lignin, modified chitin and deionized water in a mass ratio of 2-3:3-6:2-3:5-8:2-5; The cellulose polymer is obtained by mixing ethyl cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 4-8:2-6:2-6; The surfactant A is any one of N-octyl pyrrolidone, diester phosphate, and lauryl ether phosphate; The surfactant B is any one of nonionic alcohol ethoxylate, polyethyleneimine alkoxy compound and sodium perfluorononenyloxybenzenesulfonate.

2. The new energy dissolving agent according to claim 1, characterized in that: The preparation method of the modified chitin comprises the following steps: Step A1. Add hydrochloric acid to N,N-dimethylformamide, add chitin to a flask containing N,N-dimethylformamide solution acidified with hydrochloric acid, mix well, then add phthalic anhydride, heat and stir to obtain a mixture A; Step A2. Add sodium hydroxide to mixture A, stir evenly, then add phenol anhydride, heat and stir to obtain mixture B; Step A3. Sodium bicarbonate was added to the mixture B, and the gel was filtered to obtain a gel, which was washed twice with deionized water, ground and freeze-dried at -10°C for 4-4.5 hours to obtain modified chitin.

3. The new energy dissolving agent according to claim 1, characterized in that: The mass ratio of N,N-dimethylformamide, hydrochloric acid, chitin and phthalic anhydride in step A1 is 5-7:5-7:4-8:12-15; The temperature during the heating and stirring is 55-60° C., and the stirring time is 2-2.5 hours.

4. The new energy dissolving agent according to claim 1, characterized in that: In step A2, the mass ratio of the mixture A, sodium hydroxide and phenolic anhydride is 4-7:2-3:16-20; The temperature during heating and stirring is 55-60°C, and the stirring time is 2.5-3h; The mass ratio of the mixture B to sodium bicarbonate in step A3 is 5-8:7-10.

5. The new energy dissolving agent according to claim 1, characterized in that: The method for preparing the bio-based composite comprises the following steps: Polylactic acid, starch, lignin, modified chitin and deionized water are ultrasonically treated for 10-15 minutes and mixed evenly to obtain a bio-based composite.

6. The new energy dissolving agent according to claim 1, characterized in that: The molecular weight of the polyacrylic acid is 30000-50000 g / mol.

7. The new energy dissolving agent according to claim 1, characterized in that: The solvent is obtained by mixing N,N-dimethylformamide, dimethyl sulfoxide, xylene and ethanol in a mass ratio of 5-8:5-8:20-30:10-12.

8. The new energy dissolving agent according to claim 1, characterized in that: The antioxidant is obtained by mixing butylated hydroxytoluene and propyl gallate in a mass ratio of 3-7:10-15.

9. The new energy dissolving agent according to claim 1, characterized in that: The method for preparing the cellulose mixture comprises the following steps: Ethyl cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose are uniformly mixed to obtain a cellulose mixture.

10. A method for preparing a new energy dissolving agent according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1. Add the bio-based composite to a reaction kettle containing a solvent, heat to 50-60° C., stir for 40-60 min at a stirring rate of 30-60 r / min, mix evenly, then add the cellulose mixture to the solution, stir until completely dissolved, and obtain a mixture C; Step S2. Add polyacrylic acid to the mixture C, continue stirring for 20-40 minutes, then add surfactant A, surfactant B and antioxidant, stir for 55-75 minutes, and cool to room temperature to obtain a new energy disintegrator.

Citation Information

Patent Citations

  • Detergent composition

    CN106232795A

  • Digelling agent for new energy battery

    CN118562566A

  • Odor-masking coating for a pharmaceutical preparation

    WO2001049270A2

  • Saccharide sustained-release composition and preparation method therefor

    WO2024060048A1